Preface - Jerzy Maik (Fasciculi Archaeologiae Historicae, 2016)
Professor Tadeusz Poklewski-Koziełł, a retired professor at the Institute of Archaeology and Ethnology of the Polish Academy of Sciences, head of the Łódź Branch of the Institute and the editor of Fasciculi Archaeologiae Historicae, passed away while final preparations were underway for the publication of the previous fascicle. We only managed to mention the Professor’s name in the preface and include a photo of him, saying that the publication was dedicated to his memory...